The pitfalls of short-range endemism: High vulnerability to ecological and landscape traps - Mason, Leanda; Bateman, Bill; Wardell-Johnson, Grant (PeerJ, Ltd., 2018)
© 2018 Mason et al. Ecological traps attract biota to low-quality habitats. Landscape traps are zones caught in a vortex of spiralling degradation. Here, we demonstrate how short-range endemic (SRE) traits may make such taxa vulnerable to ecological and landscape traps. Three SRE species of mygalomorph spider were used in this study: Idiommata blackwalli, Idiosoma sigillatum and an undescribed Aganippe sp. Mygalomorphs can be long-lived (> 43 years) and select sites for permanent burrows in their early dispersal phase. Spiderlings from two species, I. blackwalli (n = 20) and Aganippe sp. (n = 50), demonstrated choice for microhabitats under experimental conditions, that correspond to where adults typically occur in situ. An invasive veldt grass microhabitat was selected almost exclusively by spiderlings of I. sigillatum. At present, habitat dominated by veldt grass in Perth, Western Australia, has lower prey diversity and abundance than undisturbed habitats and therefore may act as an ecological trap for this species. Furthermore, as a homogenising force, veldt grass can spread to form a landscape trap in naturally heterogeneous ecosystems. Selection of specialised microhabitats of SREs may explain high extinction rates in old, stable landscapes undergoing (human-induced) rapid change.